From local to global : eco-entrepreneurship and global engagement with the environment - Foerster, Taylor A.; Koprowski, John L.; Mars, Matthew M. (Advances in the study of entrepreneurship, innovation, and economic growth ;, 2024)
Eco-entrepreneurship is a pervasive market-based approach to environmental recovery and sustainability. The aptitudes, motivations, strategies, and overall impact of eco-entrepreneurs are well documented in relevant academic literatures. From Local to Global, Volume 30 of the Advances in the Study of Entrepreneurship, Innovation and Economic Growth series contributes to this body of work an interdisciplinary, cross-sector portrait of the various inputs and capital resources (financial, human, social), models and strategies, and current and anticipated impacts that characterize and shape eco-entrepreneurship. Composed of theoretical essays and empirical studies, the chapters span higher education innovation in the eco-tourism and recreation spaces; public policy perspectives that merges economic and entrepreneurial development, tourism, and environmental conservation; local placemaking and the development of eco-centered consumption spaces; the integration of cultural preservation and celebration with notions of sustainable entrepreneurship; the re-development of urban and industrial spaces as eco-friendly tourist destinations; and the accessibility of mainstream and eco-centered tourism mechanisms. From Local to Global provides a timely and relevant discussion and exploration of entrepreneurial topics, their impact, and ties to key values in today's society, such as social, environmental, and economic issues and challenges.